Chromosomal Q-Heterochromatin in the Human Genome - Ibraimov, Abyt (Cambridge Scholars Publisher, 2020)
The genomes of plants, animals and human consist of two components: euchromatin (representing the genes) and heterochromatin (consisting of non-coding DNAs). Unlike euchromatin, the biological role of heterochromatin is not known. To date, two types of chromosomal heterochromatin have been discovered: C- and Q-heterochromatin. C-heterochromatin is encountered in chromosomes of all higher eukaryotes, while Q-heterochromatin is present in only three higher primates: man, the chimpanzee and the gorilla. Wide variability of Q-heterochromatin has been shown to be mainly inherent in human population.